REGIONAL HEAD (PRODUCT OF A DEMOCRATIC SYSTEM) AS A ROLE MODEL AND ANTI-FRAUD REPRESENTATION - Cakra Arbas (Asia Pacific Fraud Journal, 2019)
The Constitution mandates that "Governors, Regents, and Mayors respectively as heads of provincial, regency, and municipal governments are elected democratically". In other words, the regional head is actually mandated to form a regional government as a democratic self-governing unit. The research method used is normative legal research and the types of data used are secondary data, consisting of primary legal material (various forms of legislation), secondary legal materials (data collection of scholarly work and the results research related to local election and anti-fraud systems), and tertiary legal materials (materials providing information on primary legal materials and secondary legal materials, such as dictionaries and encyclopedias). Data analysis technique used is technical qualitative analysis. In running the government mechanism, the regional head should be able to implement anti-fraud system. Anti-Fraud system is a system that monitors regulations or other mechanisms that produce some forms of report. In this case, the system offered in fact can have implications on anti fraud related to the position of regional head as a role model, that is, by bringing a great personality and optimization of thinking and action.